Coal Mine Abutment Pressure Distribution Based on a Strain-Softening Model - Li, Ang; Ma, Qiang; Ma, Li; Kang, Li; Mu, Qian; Chen, Jianbo (Frontiers in Physics, 2020)
The coal in front of mining face presents strain softening deformation characteristics. An analytical model is proposed to simulate the abutment pressure distribution over the coal in front of mining face under elastic and inelastic conditions. A new theoretical formula is derived to calculate the abutment pressure distribution and its width in elastic and inelastic regions of the coal under limit equilibrium condition. The influences of UCS, residual strength, mining height, softening modulus and deformation angle on abutment pressure distribution are discussed. The study results show that, (1) stress gradient in plastic area is larger than crushed zone; (2) the width of plastic region is independent of the peak abutment pressure, but it is dependent of UCS, residual strength, mining height, softening modulus and deformation angle; (3) the width of crushed zone in inelastic area is closely related to peak abutment pressure, coal-floor interface cohesion and friction coefficient; (4) the width of elastic zone is dependent of mining height, coefficient of horizontal pressure, coal-floor interface friction coefficient and peak abutment pressure where the coefficient of horizontal pressure has the highest impact that the width of elastic zone has logarithmic decrease with the increase of the coefficient of horizontal pressure. A case study is carried out at longwall panel 07 of No. 5 coal seam in Dongjiahe Coal Mine to verify the analytical model. The abutment pressure distribution and the widths of elastic and inelastic zones under limit equilibrium condition are calculated based on the relevant parameters. The theoretical results are compared with the field monitoring data which shows very good fit. It is proved that the proposed analytical model has high accuracy and the feasibility of the model is verified. The study results can provide guidance for similar engineering applications.